NETIZEN BEHAVIOR TOWARDS NON-CONFORMITY AND INCOMPREHENSION IN THE IMPLEMENTATION OF PANCASILA VALUES - Asy'ari, Lathifa Puteri (JURNAL SETIA PANCASILA, 2024)
Pancasila is the foundation and ideology of Indonesia since August 18, 1945. Since then, Indonesian society has followed that all state administration is based on Pancasila. Pancasila contains moral and ethical values that underlie the character of the nation. Although Pancasila guides behavior in Indonesia, including in social media, unfortunately Indonesian people do not fully understand the ethics of social media based on the values of Pancasila. Social media in Indonesia often displays messages without control and ignores ethics. This article aims to investigate how incongruence and incomprehension of Pancasila through cybercrime in social media, as well as its impact on public perception. The research method used qualitative methods, namely descriptive analytical and content analysis. The results showed the lack of awareness of Indonesian society towards social media ethics based on Pancasila values. This reveals that most perpetrators of cybercrime on social media will be trapped by Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), both intentionally and unintentionally.